A KEPERCAYAAN DAN PENDIDIKAN INFORMAL SUKU DAYAK; Studi tentang Tradisi dan Nilai-Nilai Budaya Lokal Rumah Panjang Desa Ensaid Panjang Sintang Kalimantan Barat : Studi tentang Tradisi dan Nilai-Nilai Budaya Lokal Rumah Panjang Desa Ensaid Panjang Sintang Kalimantan Barat - Karnodin; Pether Sobian (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2026)
Abstract: Informal beliefs and education in longhouses are a social fact that sounds strange today. The emergence of modern religions and formal education with superior accreditation has shaped the public's belief that this is the only way to educate. Different beliefs are considered heretical, which ultimately leads to judgmental behavior. Informal education is considered a 'lower' class education and is not taken into account. Informal beliefs and education in longhouses illustrate that in an era that glorifies technology and formal education, informal education can still be found that is effective in educating the longhouse generation in morals, ethics, mutual cooperation and concern for others. It turns out that the longhouse community is able to show concern, is more capable of working together, working together, and is not individualistic. The beliefs they believe in are true to themselves, they do not impose their beliefs on others, let alone judge the beliefs of others.